La inequidad y la concentración oligopólica en las compras públicas de software del Ecuador, periodo 2009 - 2017 - Acosta Bastidas, Diego Alfonso (2020)
The quantitative research on the oligopolistic concentration of public purchases of software, period 2009-2017, presents breadth and depth without antecedents since the approval of the Organic Law of the National System of Public Procurement, and is the only one whose main source is the basis of data from the public procurement portal of the National Public Procurement Service (SERCOP). The research also incorporates the category of the respective aspects that Law requires a systemic perspective, interrelation and multidisciplinary character, which complements its economic-political approach in the context of a social economy of knowledge on a world scale. The main conclusion of this research is the data, processed and analyzed, that proves the existence of concentration in public software purchases in Ecuador (2009-2017); with multiple consequences, such as constitutional and legal inequity, the ineffectiveness of the regulatory framework for public procurement in Ecuador and the technological incapacity of the aforementioned portal to generate alerts.